MENTAL PROCESS OF WRITING FOR ACADEMIC PURPOSES: A CASE STUDY OF INDONESIAN WRITERS - Fahrus Zaman Fadhly; Nurul Hasanah; Vina Agustiana (Indonesian EFL Journal, 2017)
This study was aimed at reconstructing the mental processes involved in academic writing. This qualitative case study involved two lecturers in University of Kuningan since they were considered able to engage mental processes in their steps of writing for academic purposes or scientific manuscript. The data were obtained through in-depth interview. As result, there are some mental processes involved in the writing activity experienced by the writers. Those mental processes are differently involved in the steps of writing starting from brainstorming, planning, drafting, revising, editing, until proofreading stage. Besides, this study revealed the ways how the writers develop their writing in case of producing a long composition without losing the essence of the paper, how the writers overcome the sticking in their writing process, the writers’ special writing features and what they expect from the reader after reading their writing. It also revealed that the differences experienced by the participants in each stage of writing are strongly influenced by their areas of interest, writing behavior and their writing style.Keywords: mental process, academic writing, stages of writing